Bioactive Diarylpentanoids: Insights into the Biological Effects beyond Antitumor Activity and Structure–Activity Relationships - Joana Moreira; Lucilia Saraiva; Madalena M. Pinto; Honorina Cidade (Molecules, 2022)
Diarylpentanoids, a class of natural products and their synthetic analogs which are structurally related to chalcones, have gained increasing attention due to their wide array of biological activities, including antitumor, anti-infective, antioxidant, anti-inflammatory, antidiabetic, anti-hyperuricemic, and neuroprotective properties. Previously, we reviewed diarylpentanoids with promising antitumor activity. However, in view of the wide range of biological activities described for this class of compounds, the purpose of this review is to provide a more detailed overview of the synthetic bioactive diarylpentanoids that have been described over the last two decades, beyond simply their antitumor effects. A total of 745 compounds were found, highlighting the main synthetic methodologies used in their synthesis as well as the structure–activity relationship studies and structural features for all activities reported. Collectively, this review highlights the diarylpentanoid scaffold as a promising starting point for the development of new therapeutic agents.